THE EFFECT OF BANK PROFITABILITY, NON PERFORMING LOAN AND BANK LIQUIDITY ON COMMERCIAL BANK VALUE ON THE INDONESIAN STOCK EXCHANGE PERIODE 2016 -2022 - Soehartanto, David (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to analyze the effect of Bank Profitability, Non-Performing Loans and Bank Liquidity on the Value of Commercial Banks Listed on the Indonesia Stock Exchange for the 2016 - 2022 period. The populations in this study were all Commercial Bank companies listed on the IDX for the 2016 - 2022 periods, totaling 40 companies. . Then, the samples were analyzed using purposive sampling method to obtain 21 companies. The analytical method used is panel data regression with Eviews 10 software. The results show that bank profitability has a positive and significant effect on the value of Commercial Banks listed on the IDX, non-performing loans have a negative and significant effect on the value of Commercial Banks listed on the IDX, and liquidity does not have a significant effect on the value of Commercial Banks listed on the IDX